Speed 2 cruise control - Bont, Jan de.; Nathanson, Jeff.; Bullock, Sandra; Patric, Jason; Dafoe, Willem; Twentieth Century Fox.; Blue Tulip Productions ([Los Angeles, Calif.] Twentieth Century Fox, 1997)
Annie Porter is thrilled when her boyfriend Alex Shaw presents her with two tickets for a cruise to the Bahamas on a Norwegian luxury liner. The trip is a peace offering presented because Annie has just learned that Alex is a police officer who's been lying to her about his choice of profession. Alex lied because Annie didn't want to date any more cops after what happened with the bus in Los Angeles. The cruise ship's passengers include members of a diamond dealers' association, who have filled the ship's vault with valuable diamonds. Little do they know that passenger John Geiger, the designer of the ship's computer system, has planned to take over the ship, steal the diamonds, and set the ship on a collision course with an oil tanker anchored at the island of St. Martin. Geiger was fired and cast aside by the computer company he worked for, and he wants revenge. Now it's up to Alex to stop him.
Title from container.
"Exclusively distributed in the Philippines by Viva Video"--Container.
Originally released as motion picture.
Summary from the website: http://www.imdb.com/title/tt0120179/plotsummary.
Story, Jan de Bont and Randall McCormick ; screenplay, Jeff Nathanson ; editor, Alan Cody ; producers, Steve Perry, Michael Peyser ; director, Jan de Bont.
Sandra Bullock, Jason Patric, Willem Dafoe.
Keywords: Cruise ships -- Drama; Action and adventure films; Suspense in motion pictures, television, etc; Feature films; Film sequels; Bahamas -- Action